Disrupted social integration: A case study of Shanghai's point-seeking group. (June 2021) - Huang, Yixiong; Yang, Shufei; Wang, Kuiming
The development and expansion of Shanghai have attracted many labor migrants. Because the migrants hold a non-local hukou (household registration), they can only access minimal social services in urban areas. One of the reforms introduced by the local government of Shanghai is the Residential Points System (RPS), which would allow qualified migrants to access more social services. The policy has created a new social class: the "point-seeking group" (PSG), which refers to migrants who try to obtain urban social benefits through the points-earning clauses of the RPS. This study examines the integration experiences of the PSG in Shanghai. Findings from the study suggest that the PSG has encountered "disrupted social integration" in which institutional constraints pose a major barrier to the economic and social integration of first- and second-generation migrants.